A representação da Dengue em Livros Didáticos de biologia utilizados em escolas públicas no município de Uruguaiana - RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Dengue is a public health problem, since the number of cases of the disease rises every year. This is due to favorable conditions for mosquito breeding in the country. It is an infectious disease transmitted by the Aedes genus mosquito, the most common Aedes aegypti. Assuming that education emerges as a strong ally in combating the proliferation of the mosquito and disease, this research aims to analyze two collections of textbooks Biology used by the public education in the city of Uruguaiana / RS. The issue of verification of choice in textbooks should, for this to be a resource widely used within the educational process, and sometimes the only teaching tool the teacher. Only two books present an approach to the topic dengue. From this, the results find that the related dengue contents are presented in the books of brief and incomplete, difficult to understand and practices related to the theme.
Keywords: Dengue; Aedes aegypti; Science of nature; Livro didático; Textbook; Uruguaiana; Ciências da Natureza; CNPQ::CIENCIAS HUMANAS